PENGARUH PEMANFAATAN PERPUSTAKAAN TERHADAP PENINGKATAN MINAT BACA SISWA DI SDN 136 PEKANBARU TAHUN PEAJARAN 2014/2015 - Siagian, Nova Siagian; Marhadi, Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Of observations by the author in library SDN 136 Pekanbaru it can be seen that the facilities and infrastructure available in the library SDN 136 Pekanbaru full available, one of which is the provision of textbooks. Based on the answers to questionnaires given to students, that the library has a maximun utilization. It can be seen from all collections of books borrowed can assist students in learning activities, books borrowed, in the search and was taken by the students themselves as well as a comfortable reading room make students interested in reading book in the library SDN 136 Pekanbaru. High students wishes to obtaim reading material is increasing, the need for information is increasing and increasing learning achievement after the use of the various services available in the library SDN 136 Pekanbaru. Influence between the use of the library to increase students interest in reading simultaneously (Uji F). Based test simultaneously obtainable  = 44,846 the contribution of  37,4%. Keyword: Use of Libraries,  Students’ Reading Interest